Pareamento para padronização inicial de amostra em pesquisas de endodontia usando microtomografia computadorizada e tomografia computadorizada de feixe cônico - Lima, Jennyffer Samira de (2021)
The aim of this study was to evaluate the use of cone-beam computed tomography (CBCT) as an alternative method of computed microtomography (micro-CT) for the pairing and initial standardization of samples in ex vivo polls in endodontics. The palatine channels of 28 first superior permanent molars were selected. All samples were submitted to CBCT and micro-CT. The area of interest was standardized at 9mm measured from the apical forame towards the region of furca. In the micro-CT and CBCT the total volume, the area and the linear mesial measurements for distal (M-D) and vestibular for palatine (V-P) were determined; All measures were carried out by a single operator in two different times (T1 and T2). To evaluate the replicability of the observer for the two measurements carried out (T1 and T2) the Student t-test was applied for paired samples and estimated the intraclass correlation coefficient (ICC), considering the mixed effects model for consistency analysis with in average. The significance of the bias was evaluated using the Student t test for paired samples or the non-parametric Wilcoxon test. Values of p <0.05 indicated statistical significance. The results of the replicability of the observer on the two measures carried out presented the ICC> 0.90 being considered as of excellent reliability. Already in the evaluation of the quality of the CBCT measures considering the micro-CT measurements as a gold standard, the value of P showed that there was a statistically significant difference between the two methods and the value of ICC <0.50, which demonstrates a low reliability of CBCT to determine the measures. It can be concluded, that the methods, micro-CT and CBCT, were discordant, that CBCT was not an effective method for the initial pair of samples in laboratory research in endodontics using ex vivo human teeth.